Digital Divide : How Technology Access Impacts Community Colleges across the United States during a Pandemic / Jacob B. Bray. - Bray, Jacob B. (Distributed by ERIC Clearinghouse, 2021)
"Digital Divide: How Technology Access Impacts Community Colleges Across the United States During a Pandemic" looks at the current state of the digital divide in the United States and how it is affecting community college students during the COVID-19 pandemic. Leaders at community colleges in Spokane, Washington, Los Angeles, California, and on the Navajo Reservation were interviewed to show what the digital divide looks like in an urban, a suburban, and a rural community and how it is affecting each college's students. While all colleges are faced with different circumstances, similarities emerge as the digital divide impacts students across the country. The paper also looks at how the Coronavirus Aid, Relief, and Economic Security (CARES) Act impacted the digital divide within the community college sector.